2004
DOI: 10.1016/j.femsec.2004.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and morphological responses of the soil bacterium Rhodococcus opacus strain PD630 to water stress

Abstract: Rhodococcus opacus PD630 was investigated for physiological and morphological changes under water stress challenge. Gluconate- and hexadecane-grown cells were extremely resistant to these conditions, and survival accounted for up to 300 and 400 days; respectively, when they were subjected to slow air-drying. Results of this study suggest that strain PD630 has specific mechanisms to withstand water stress. Water-stressed cells were sensitive to the application of ethanol, high temperatures and oxidative stress,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 46 publications
3
52
0
4
Order By: Relevance
“…The increase in number of microbial cells is consistent with the reported increase in microbial biomass in a California grassland over the dry summer (Parker and Schimel, 2011). This is also consistent with previous work showing bacterial cell division and down-sizing in response to desiccation as well as starvation (Potts, 1994;Alvarez et al, 2004).…”
Section: Bacterial and Fungal Community-level Responsesupporting
confidence: 91%
“…The increase in number of microbial cells is consistent with the reported increase in microbial biomass in a California grassland over the dry summer (Parker and Schimel, 2011). This is also consistent with previous work showing bacterial cell division and down-sizing in response to desiccation as well as starvation (Potts, 1994;Alvarez et al, 2004).…”
Section: Bacterial and Fungal Community-level Responsesupporting
confidence: 91%
“…Physiological studies analysing the accumulation and mobilization of storage lipids in Rhodococcus sp. showed that TAGs serve as a depot for carbon and energy in these bacteria (Alvarez et al, 2000(Alvarez et al, , 2004Alvarez & Steinbüchel, 2002). Strain PD630 can be considered as an oleaginous micro-organism, since TAGs can account for up to 76 or 87 % of the cellular dry weight in gluconate-or olive-oil-grown cells, respectively (Alvarez et al, 1996;Voss & Steinbüchel, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the actinomycetes, particularly Streptomyces and Rhodococcus, reportedly accumulate lipid inclusion bodies during the stationary phase of growth (Alvarez & Steinbuchel, 2002). Bacteria have been shown to use these stored substances as a sole source of carbon and energy during prolonged starvation (Alvarez & Steinbuchel, 2002;Alvarez et al, 2004). Inclusion bodies were also present in the 7-month-old SAA cells, and the rod cells measured 0.5-0.85 mm60.45 mm in size (Fig.…”
Section: Tem Observations Of Saamentioning
confidence: 94%